The Food Safety Modernization Act: a summary of the act, education, and implementation. - Pineda, Caitlin Emily (Kansas State University, 2018)
Since the Food Safety Modernization Act (FSMA) was signed into law in 2011, the government has taken huge strides toward making the food safety system preventive rather than reactive. Specifically, the Preventive Controls for Human Food (PCHF) final rule has required collaboration from government officials, educational institutions, industry professionals, and stakeholders to assist in the rulemaking, education, and implementation of the new rule. The rulemaking process for the PCHF final rule took 4 years to finalize. The Food and Drug Administration funded a grant to the Illinois Institute of Technology’s Institute for Food Safety and Health (IIT IFSH) to help create an educational program about food safety risk-based preventive controls. Since then, the Food Safety Preventive Controls Alliance (FSPCA) has been coordinating training programs to certify food professionals as Preventive Controls Qualified Individuals (PCQI). After gathering minor statistical evidence through course evaluations for 10 FSPCA facilitated education programs, extension personnel of the Food Science Institute at Kansas State University found that the educational materials are a big help to those in industry and in regulatory agencies.
Keywords: FSMA; FSPCA; Food safety; Preventive controls